Una Combinación y tres especies nuevas de Lichenochora (Phyllachorales, ascomicetes liquenícolas), y notas adicionales para el género - Etayo Salazar, Javier; Navarro-Rosinés, Pere (Revista Catalana de Micologia, 2011)
A new combination and three new species of Lichenochora (phyllachorales, lichenicolous Ascomycota), and additional reports for the genus. Three species of the genus Lichenochora (Phyllachorales, not lichenized lichenicolous ascomycetes) are decribed as new to science: L. aipoliae Etayo, Nav.-Ros. et Coppins sp. nov., that grows on Physcia aipolia, L. coppinsii Etayo et Nav.-Ros. sp. nov., on Protopannaria pezizoides, and L. paucispora Etayo et Nav.-Ros. sp. nov., on Bilimbia sabuletorum. A new combination to the genus is proposed: L. lepidiotae (Anzi)Etayo et Nav.-Ros. comb. nov., on Fuscopannaria praetermissa. The description of the anamorph of Lichenochora epidesertorum is included. Raports of known range extensions for different species of the genus: L. constrictella is mentioned by first time for continental America (USA) and L. aprica for Spain. An identification key to the species of Lichenochora are included.